International Child Abduction in the Framework of the Hague Conference on Private International Law - Mohammed, Fatima; Abed, Mustafa (Journal of Legal Sciences, 2023)
The prevailing pattern of child abduction has changed in the current era, and is no longer limited to the local borders of states but is taking an international turn, and the most accurate legal use of the term international child abduction originates in the Hague Convention on the Civil Aspects of International Child Abduction, which considers-as the naming of the convention suggests - In cases of kidnapping from the point of view of private international law, the essence of it is a bitter dispute over custody rights that develops to the point of abducting children across borders, to try to obtain custody of the child in another country, so that the snap here is a family member and most often a parent, as it causes many legal consequences and a traumatic impact on the abducted child, who is in a situation where he is struggling with a range of emotions. In line with the above, this research clarifies what it means to kidnap a child by a family member by analyzing the concept of international child abduction in the first research, while in the second section we will show the available mechanisms to combat it.